Crop geometry and fertility levels influence seed productivity, profitability and irrigation water use efficiency of dwarf Indian mustard - S.S. Rathore; Kapila Shekhawat; R.K. Singh (Annals of Agricultural Research, 2022)
The experiment on different crop geometry and fertility levels were conducted split plot design with three replications during 2015-16 and 2016-17 for dwarf Indian mustard (Brassica juncea) NPJ 176 with the objective to find out optimum seed yield, irrigation water use efficiency and economics. The narrower crop geometry 20 × 20 cm and 20 × 10 cm have higher secondary branching, main shoot length (cm) , seeds per siliqua and total number of siliqua,/plant. With the increasing levels of fertility (at 125% and 150% RDF) most of the growth and yield attributes increased. Significantly higher seed and biological yield was obtained at narrow crop spacing (20 × 10 cm and 20 × 20 cm) in RDF, 125% RDF and 150% RDF. The fertility levels and crop geometry showed that higher seed yield was obtained at 150 RDF at 20 × 20 cm crop geometry. Higher irrigation water use efficiency (IWUE) was observed at 20x10 cm and 20x20 cm crop geometry. Maximum IWUE of 20.4 kg/hamm was observed at 20 × 20 cm crop geometry in 150% RDF.The higher gross, net returns, B:C ratio and profitability were observed at 20 × 10 cm and 20 × 20 cm crop geometry. The economics in terms of net return/ha also reflects that fertility levels of 150% RDF resulted in higher benefit at 20 × 20 cm and 20 × 10 cm crop spacing.